Konstruktive Galoistheorie - Matzat, Bernd Heinrich (Lecture notes in mathematics, 1987)
This volume is based on a lecture course on constructive Galois Theory given in Karlsruhe by the author. The purpose of the course was to introduce students to the methods developed in the past few years for the realisation of finite groups as Galois groups over Q or over abelian number fields. Thus the book is addressed primarily to students with algebraic interests, as seminar material. Specialiists also will find in it a multitude of examples of polynomials with special Galois groups, which can of course also be used for the usual algebra courses